The Pattern of International Trade Between Japan and the Pacific Basin Countries : A Comparison Between 1975 and 1985 - Shirai, Sayuri (IMF Working Papers; Working Paper ;, 1995)
Using the international input-output tables between Japan and five Pacific Basin countries (Indonesia, Korea, Malaysia, Singapore, and Thailand) for the years 1975 and 1985, the paper examines the trade structure in 1975 and how it had shifted by 1985. It shows that intra-industry trade in manufactured products expanded as Japan increased imports of more capital-intensive products from these countries. Intra-industry trade of intermediate inputs increased substantially more than of final products, reflecting a trend by manufacturers to subdivide the production process of intermediate inputs and to shift their locations to different countries. This suggests a more active development of international labor in the intermediate stages of production and a deepening of regional linkages.